Probing the nuclear import signal and nuclear transport molecular determinants of PRV ICP22. Issue 1 (December 2016) - Cai, Mingsheng; Jiang, Si; Zeng, Zhancheng; Li, Xiaowei; Mo, Chuncong; Yang, Yanjia; Chen, Chunke; Xie, Peiping; Bian, Yun; Wang, Jinlin; Huang, Jinlu; Chen, Daixiong; et al.
Abstract Background Herpes simplex virus 1 (HSV-1) ICP22 is a multifunctional protein and important for HSV-1 replication. Pseudorabies virus (PRV) ICP22 (P-ICP22) is a homologue of HSV-1 ICP22 and is reported to be able to selectively modify the transcription of different kinetic classes of PRV genes, however, the subcellular localization, localization signal and molecular determinants for its transport to execute this function is less well understood. Results In this study, by utilizing live cells fluorescent microscopy, P-ICP22 fused to enhanced yellow fluorescent protein (EYFP) gene was transient expressed in live cells and shown to exhibit a predominantly nucleus localization in the absence of other viral proteins. By transfection of a series of P-ICP22 deletion mutants fused to EYFP, a bona fide nuclear localization signal (NLS) and its key amino acids (aa) of P-ICP22 was, for the first time, determined and mapped to aa 41–60 (PASTPTPPKRGRYVVEHPEY) and aa 49–50 (KR), respectively. Besides, the P-ICP22 was demonstrated to be targeted to the nucleus via Ran-, importin α1-, and α7-mediated pathway. Conclusions Our findings reported herein disclose the NLS and molecular mechanism for nuclear transport of P-ICP22, these results will uncover new avenues for depicting the biological roles of P-ICP22 during PRV infection.